Healthcare workers infected with COVID-19 in a tertiary care center in Kerala - Dev, Sahya S.; Abhraham, Joe; Varghese, Abraham V. (International Journal Of Community Medicine And Public Health, 2022)
Background: Health care workers are at the forefront of the fight against COVID-19. There is a high risk of them contracting the infection and then transmitting it to vulnerable patients and colleagues. Therefore, it is critical to investigate the prevalence and risk factors among HCWs. This study describes the characteristics of healthcare workers who tested positive for COVID-19 in a tertiary care hospital in India. Methods: A cross-sectional study was conducted among HCWs from a tertiary care center with a real-time - polymerase chain reaction (RT-PCR) test positive for COVID-19 on a nasopharyngeal swab from July 2020 to January 2021. All healthcare workers with confirmed SARS-CoV-2 infection were contacted over the telephone to collect data regarding their probable source of contact, usage of personal protective equipment, and clinical course. Their treatment history was extracted using electronic health records. Results: During the study period, 192 HCWs were RT-PCR positive for COVID-19. The mean age of the study participants was 34.01 years. Among the infected, 23.4% were male employees, while the remaining 76.6% were female employees. Nurses were most commonly affected (36.5%), followed by doctors (22.9%) and housekeeping staff (15.6%). Infected HCWs acquired the infection from the hospital in 73.4% of cases, while 38.6% had direct contact with patients or colleagues. Conclusions: HCWs have an increased risk of COVID-19 infection at the workplace. Strengthening of infection control measures as well as strict follow-up of precautionary measures needs to be ensured, even during break time and work hours.